2014
DOI: 10.1155/2014/581876
|View full text |Cite
|
Sign up to set email alerts
|

Pancoast’s Syndrome due to Fungal Abscess in the Apex of Lung in an Immunocompetent Individual: A Case Report and Review of the Literature

Abstract: Malignant tumours in the apices of the lungs, especially bronchogenic carcinoma (Pancoast tumours), are the most common cause of Pancoast' syndrome which presents with shoulder or arm pain radiating along the medial aspect of forearm and weakness of small muscles of hand with wasting of hypothenar eminence due to neoplastic involvement of C8 and T1 and T2 nerve roots of brachial plexus. There are a number of benign conditions which may lead to Pancoast's syndrome; fungal abscess located in the apex of lung is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Similar to us, Das et al reported a case of Pancoast tumour caused by pulmonary aspergillosis in an immunocompetent individual who presented with complaints similar to our patient. 12 But contrary to our case, microbiological examination of the FNAC sample was negative and the authors had to proceed with a trucut biopsy of the lesion to arrive at the diagnosis. Guidelines recommend histopathological examination of lung tissue to make a diagnosis of pulmonary aspergillosis, due to the poor sensitivity of sputum and bronchial lavage specimens.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Similar to us, Das et al reported a case of Pancoast tumour caused by pulmonary aspergillosis in an immunocompetent individual who presented with complaints similar to our patient. 12 But contrary to our case, microbiological examination of the FNAC sample was negative and the authors had to proceed with a trucut biopsy of the lesion to arrive at the diagnosis. Guidelines recommend histopathological examination of lung tissue to make a diagnosis of pulmonary aspergillosis, due to the poor sensitivity of sputum and bronchial lavage specimens.…”
Section: Discussioncontrasting
confidence: 85%
“…Treatment options include oral itraconazole and intravenous amphotericin B, and complete resolution of the lesion can be seen with treatment. 12…”
Section: Discussionmentioning
confidence: 99%